Correlation of Learning Methods with Learning Styles of Junior High School Students in Bulukumba Regency - Nurdin Kaso; Ervi Rahmadani (Pusat Studi Bahasa dan Publikasi Ilmiah, 2022)
This study was conducted to determine the application of learning methods to verify students' learning styles in Indonesian language learning and to determine whether or not there is a correlation between the two variables. In this study, only focused on 4 research locations, namely SMP Negeri 2 Bulukumba, SMP Negeri 1 Bulukumba, SMP Negeri 3 Bulukumba, and SMP Negeri 5 Bulukumba. This research uses quantitative research with a population of 1010 grade IX students and samples as many as 100 students. Data collection using library research and field research. The data analysis used the percentage formula, mean score, and Pearson product-moment correlation. The results showed that: From the results of the correlation analysis, there is a relationship of 0.894 between the two variables, with a determinant coefficient of 78%. means that the correlation between the two variables is very strong, while 22% is another influencing factor. Therefore, Ho is rejected and H1 is accepted. This means that there is a significant relationship between learning methods and the learning styles of grade IX students of SMP Negeri in the Bulukumba Regency. 8 which is closer to number 4 with a good category. 3) From the results of the correlation analysis, there is a relationship of 0.894 between the two variables, with a determinant coefficient of 78%. means that the correlation between the two variables is very strong, while 22% is another influencing factor. Therefore, Ho is rejected and H1 is accepted. This means that there is a significant relationship between learning methods and the learning styles of grade IX students of SMP Negeri in the Bulukumba Regency. 8 which is closer to number 4 with a good category. 3) From the results of the correlation analysis, there is a relationship of 0.894 between the two variables, with a determinant coefficient of 78%. means that the correlation between the two variables is very strong, while 22% is another influencing factor. Therefore, Ho is rejected and H1 is accepted.